2022
DOI: 10.1111/apa.16354
|View full text |Cite
|
Sign up to set email alerts
|

National cohort of infants born before 24 gestational weeks showed increased survival rates but no improvement in neonatal morbidity

Abstract: Aim To describe survival and neonatal morbidities in infants born before 24 weeks of gestation during a 12‐year period. Methods Data were retrieved from national registries and validated in medical files of infants born before 24 weeks of gestation 2007–2018 in Sweden. Temporal changes were evaluated. Results In 2007–2018, 282 live births were recorded at 22 weeks and 460 at 23 weeks of gestation. Survival to discharge from hospital of infants born alive at 22 and 23 weeks increased from 20% to 38% (p = 0.006)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 47 publications
1
19
0
Order By: Relevance
“…A national Swedish study by Lundgren et al reported that the number of infants born before 24 weeks who survived to 40 weeks of postmenstrual age doubled from 2007 to 2018 1 . However, neonatal morbidity rates did not change.…”
Section: Life Support Decisions At the Limit Of Viabilitymentioning
confidence: 98%
“…A national Swedish study by Lundgren et al reported that the number of infants born before 24 weeks who survived to 40 weeks of postmenstrual age doubled from 2007 to 2018 1 . However, neonatal morbidity rates did not change.…”
Section: Life Support Decisions At the Limit Of Viabilitymentioning
confidence: 98%
“…1 Survival among live-born infants at 22 to 23 weeks' gestational age (GA) ranged from 10% to 38% during the same period. 1,2 Expert groups have varying recommendations on active resuscitation and provision of neonatal f Included no charge or other expected primary payers.…”
Section: Association Of Survival At 22 Weeks' Gestation With Use Of A...mentioning
confidence: 99%
“…For every maternal death in the US, 1 approximately 60 pregnant individuals experience severe maternal morbidity (SMM), 2 an indicator of poor maternal outcomes and risk factor for mortality. Black individuals are twice as likely to experience SMM as White individuals, 3 mirroring disparities in maternal deaths.…”
Section: Associations Between State-level Changes In Reproductive Hea...mentioning
confidence: 99%
See 1 more Smart Citation
“…In this issue of Acta Paediatrica, Lundgren et al publish the Swedish experience on neonatal outcome after adopting proactive obstetric and neonatal interventions to salvage infants born as early as GA 22 and 23 weeks. 1 During 2007-2018, the stillbirth rate decreased for infants with GA 22 weeks, and the survival rates of liveborn infants increased from 19% to 38% for GA 22 weeks and from 45% to 67% for GA 23 weeks. The largest increase occurred from 2016 when a new national guideline stated that neonatal resuscitation should be considered from GA 22 weeks and recommended from 23 weeks.…”
mentioning
confidence: 99%